2019
DOI: 10.1039/c9tb00992b
|View full text |Cite
|
Sign up to set email alerts
|

Preventing fungal growth on heritage paper with antifungal and cellulase inhibiting magnesium oxide nanoparticles

Abstract: Magnesium oxide nanoparticles (MgO NPs) as a colourless antifungal treatment with anti-cellulase activity to prevent biodeterioration of paper-based heritage objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Many papers have proposed using NPs to prevent rather than control biodeterioration. Franco Castillo and colleagues [ 34 ] investigated magnesium oxide nanoparticles to protect 18th century papers from fungi without altering the appearance of the samples. Zarzuela et al [ 35 ] developed, via a sol–gel route, CuO/SiO 2 nanocomposites as protective coatings for built heritage.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Many papers have proposed using NPs to prevent rather than control biodeterioration. Franco Castillo and colleagues [ 34 ] investigated magnesium oxide nanoparticles to protect 18th century papers from fungi without altering the appearance of the samples. Zarzuela et al [ 35 ] developed, via a sol–gel route, CuO/SiO 2 nanocomposites as protective coatings for built heritage.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Suspensions of conidia were prepared from A. flavus-containing potato dextrose agar (PDA) plates grown for eight days by rubbing the sporulating surface with a bent needle. After filtering through a 60 µm mesh sieve to remove debris, sterile distilled water was added to the suspension to reach a concentration of 10 7 conidia/mL [38,39], based upon cell counts using a hemacytometer.…”
Section: Aspergillus Flavus Suspensionmentioning
confidence: 99%
“…Besides the measures that attempt to fix the physical environment, NPs such as silver (Ag), zinc oxide (ZnO), titanium dioxide (TiO 2 ) and magnesium oxide (MgO) NPs have been widely applied to prevent mold contamination on paper, stone, paintings and wooden materials as stressors during the last decade because of their abilities to interact with DNA and proteins and pass through the cell membrane as well as their low cytotoxicity (Gaylarde et al 2011; Franco Castillo et al 2019). Different mechanisms have been proposed for these NPs.…”
Section: Currently Adopted Mold Control Measures and Their Limitationsmentioning
confidence: 99%
“…Moreover, in paper conservation, NPs are particularly of interest due to their ability to effectively cover the paper and penetrate into the cellulose fibre network to neutralize acids, acting to protect paper from cellulose hydrolysis. Franco Castillo et al (2019) have demonstrated the feasibility of using MgO NPs as colourless, low cost and effective anti‐mold materials to prevent fungal contamination on 18th‐century paper.…”
Section: Currently Adopted Mold Control Measures and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation